Innovative Strategies for Teaching and Learning of Business Education in Universities in South East, Nigeria - Olawoyin, Rasheed Olawale; Adeniji, Alex (International Business Education Journal, 2025)
The present study aimed to explore novel approaches to the instruction and acquisition of Business education within universities located in the South East region of Nigeria. Three research inquiries were posited, including the formulation of three null hypotheses. The study employed a descriptive survey research design. The study involved 79 business educators from eight South-East Nigerian colleges offering business education programmes, and the entire population formed the sample size. The study utilized a validated structured questionnaire called the "Questionnaire on Innovative Strategies in Teaching and Learning of Business Education Programme" (QISTLBEP). This questionnaire was constructed by the researcher, drawing insights from relevant literature. The instrument comprised two distinct portions, namely A and B. Section A comprises two items on the demographic data of the respondents, whilst Section B encompasses a total of 24 items that are organized into three clusters, denoted as I, II, and III, in accordance with the research questions. The test was administered to a sample of 10 lecturers from the business education department at Delta State University, Abraka, who were not included in the study population. The collected data underwent analysis utilizing the Cronbach Coefficient Alpha to assess the internal consistency of the instrument. The resulting reliability coefficient values for cluster I, II, and III were 0.86, 0.77, and 0.78, respectively. The research topics were addressed by employing descriptive statistics, specifically the mean and standard deviation, to assess the homogeneity of the respondents’ opinions. The inferential statistics of the t-Test were employed to evaluate the null hypotheses at a significance level of 0.05. The results of the study indicated a consensus among business educators regarding the utilization of experiential strategies for the instruction and acquisition of business education courses. However, there was a lack of agreement among these educators regarding the implementation of team-related and flipped strategies for the teaching and learning of business education courses in public universities located in the South East region of Nigeria. Based on the research outcomes, it is advised that the different departments of Business Education in public universities in South East Nigeria should adopt experiential strategies. This approach aims to enhance business students’ skill development through practical involvement and foster their engagement in the course.